A Study on the Factors having Significant Impact on the Reputation of the Business Higher Educational Institutions - B, Anusha; BI, Sogara (International Journal of Psychosocial Rehabilitation, 2020)
Background: The concept of Branding in service sector has amplified its popularity since a decade. Educational Institutions are facing certain challenges related to choices made by students to pursue their Higher Studies. Students give priority to those institutions that have high reputation and reputation is determined by various other factors. However, building a reputation comes along with building a good Brand Image. Aim/ Methodology: This study targets at recognizing the factors that influence reputation of the Higher Educational Institutions using Co-variance analysis, and to evaluate and analyze the significance impact of the input factors on the output (Reputation) factor using Linear Regression Model. Findings: The study identified 37 variables that were grouped into seven constructs based on their characteristics. These constructs were tested using co-variance analysis and results showed a good-fit to carry on the research further. Further, the results of Linear Regression Modelling showed a positive significance impact for Career Development and Placement, Research culture, Location and Infrastructure and Extra and co-curricular activities on reputation of the HEI. Conclusion: The HEIs must give most priority to conduct activities relating to career development and placement opportunities for students like exchange programs, inviting top companies with good job profiles, industry interaction, industry tie-ups/ linkages, etc. further, study can focus on the reputation factors from other stakeholders’ perspective.